Varietas in the Variae: Erudition and Audience in Cassiodorus’ Epistles (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
Cassiodorus’ Variae has been the centre of a range of scholarly debates, particularly with regard to the nature and originality of its encyclopaedic passages. This paper argues that these passages were not falsified ornamentation but part of Cassiodorus’ original chancery rhetoric, this style being influenced by ‘jewelled’ contemporary literary aesthetics. On the basis of a catalogue of these digressive references and disquisitions, it is shown that Cassiodorus modified the appearance, content, and length of these passages based on a letter’s original audience and context. This is illustrated by the interpretation of patterns in letters to the major constituent groups that received the Variae’s letters, including Roman senators, Ostrogoths, the kings of Germanic successor states, the Roman court at Constantinople, and the clergy. The paper concludes by offering comments on potential future research directions, the study’s implications for Cassiodorus’ role as Quaestor, and the ends to which he compiled the Variae.